Enhancing biology concept mastery and metacognitive awareness through problem-based learning with concept mapping in a coffee plantation area - Suratno, Suratno; Ningrum, Rafi'a Sastra; Wahono, Bevo (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
This study addresses empirical learning problems found in senior high schools located in coffee plantation areas, where students tend to show low mastery of biology concepts and limited metacognitive awareness due to conventional, teacher-centered instruction. The study aims to examine the effect of Problem-Based Learning (PBL) integrated with concept mapping on students’ biology concept mastery and metacognitive awareness. A quantitative approach with a quasi-experimental pretest–posttest nonequivalent control group design was employed. The research was conducted at SMA Negeri Jenggawah, Jember Regency, involving 69 tenth-grade students, consisting of 35 students in the experimental class and 34 students in the control class. Data were collected using a biology concept mastery test and a metacognitive awareness inventory adapted from Schraw and Dennison. The data were analyzed using ANCOVA after fulfilling normality and homogeneity assumptions. The results indicated that PBL integrated with concept mapping had a significant effect on students’ biology concept mastery, but did not significantly affect their metacognitive awareness. These findings suggest that PBL with concept mapping is effective in improving conceptual understanding, although longer and more intensive implementation is required to optimally enhance metacognitive awareness. This study recommends the integration of contextual environmental problems and structured reflective activities to support metacognitive development.